Experimental Studies on Flexural Behaviour of RC Beams Reinforced with Basalt Rebars (Global Journals of Research in Engineering, 2022)
The Paper covers utilization of Basalt rebar for concrete reinforcing its comparatively new element which seems a potential material for infrastructural reinforcing Superior temperature endurance and low weight are only some of the advantages it offers above other composites and steel Because it is non-corrosive basalt rebar is an excellent option for reinforcing concrete constructions that are located near sea The work describes several experimental studies like a tensile strength testing of basalt rebar with standard steel as well as flexure strength test of beams reinforced both by basalt rebar and traditional steel also work is being done for identifying material qualities mixture ratio of M20 grade concrete as well as standard cubes were tested in compression as well as prisms are examined for flexural strength There are 12 samples of 1500 150 230mm 1500 mm that have been cast and monitored under a 1000kN capacity load frame Six of the specimens have standard steel reinforcement while the other six have basalt reinforcement Rebar with diameters of 10mm and 12mm is often utilized The patterns of crack development with load deflection are being studied in this research project Tensile strength of basalt rebar is double that of standard steel according to results of experiments When comparing basalt-reinforced beams with steel-reinforced beams the load deflection curve the first crack load the maximal load as well as deflections are all taken into consideration Conventional beams with basalt-reinforced beams have similar ultimate load-carrying capability Deflection in basalt reinforced beams is 66 66 percent lower than in normal beams according to the research Failure of conventional RC beams was determined to be based on flexure criteria but the failure of basalt reinforced RC beams was based on the expansion of shear crack
Keywords: basalt rebar; steel; flexural behavior; reinforced concrete beams